Understanding the Impacts of Pyrolysis Temperature on the Energy Performance of Eucalyptus spp. Charcoal - Allana Katiussya Silva Pereira; Dalton Longue Júnior; Álison Moreira da Silva; Elias Costa de Souza; Fabíola Martins Delatorre; Brunela Pollastrelli Rodrigues; Ananias Francisco Dias Júnior (Environmental Sciences Proceedings, 2021)
This study aimed to investigate the influence of two pyrolysis temperatures (300 °C and 450 °C) on the energy quality of charcoal using a mix of commercial eucalypt woods. In this study, pyrolysis was carried out at a heating rate of 3.33 °C.min−1 for a duration of 3 h. The apparent density, bulk density, immediate analysis, high heating value, energy density, and combustibility index of the charcoal were measured. Under the conditions analyzed, pyrolysis performed at a final temperature of 450 °C resulted in charcoal with better energy performance than that produced at 300 °C.